Experimental Studies on the Mechanical Properties of Loess Stabilized with Sodium Carboxymethyl Cellulose - Hongwang Ma; Qi Ma (Advances in Materials Science and Engineering)
This research investigated the use of sodium carboxymethyl cellulose (CMC) as a reinforcement to improve mechanical properties of loess soil found in northwestern China. The mechanical properties of loess were determined by unconfined compressive strength and split tensile strength tests. Three different contents of CMC were adopted: 0.5%, 1.0%, and 1.5%. The results showed that utilizing CMC reduced the maximum dry density of the loess. The compressive strength, tensile strength, and Young’s modulus are enough to construct low-rise buildings when the CMC content exceeds 1.0%, based on existing standards. This research thus provides a prospective sustainability method for loess stabilization.